Japanese nationwide questionnaire survey on delayed cerebral infarction due to vasospasm after subarachnoid hemorrhage - Nishikawa, Yusuke; Yamada, Shigeki; Uchida, Mitsuru; Yamanaka, Tomoyasu; Hayashi, Yuki; Katano, Hiroyuki; Tanikawa, Motoki; Iwama, Toru; Iihara, Koji; Morioka, Motohiro; Mase, Mitsuhito (Frontiers in Neurology, 2023)
Background and purpose Various prophylactic drugs for cerebral vasospasm and delayed cerebral infarction (DCI) after subarachnoid hemorrhage (SAH) have been used in Japan. To investigate the treatment trends for cerebral vasospasm and frequency of DCI after SAH throughout Japan in 2021. Methods In 2021 we conducted an anonymous questionnaire survey on management for preventing cerebral vasospasm after aneurysmal SAH, and the frequency of DCI. The questionnaire was emailed to 955 certified neurosurgeons at 553 hospitals in Japan. Of them, 162 hospitals (29% response rate) responded to the questionnaire. Of these, 158 were included in this study, while four hospitals that responded insufficiently were excluded. The efficacy of treatments for reducing DCI were examined through a logistic regression analysis. Results Among 3,093 patients treated with aneurysmal SAH, 281 patients (9.1%) were diagnosed with DCI related to cerebral vasospasm. Coil embolization had significantly lower DCI frequency (6.9%), compared to microsurgical clipping (11.8%, odds ratio, 0.90; 95% confidential intervals, 0.84–0.96; P, 0.007). In addition, cilostazol administration was associated with significantly lower DCI frequency (0.48; 0.27–0.82; 0.026). The efficacy of cilostazol in reducing DCI remained unchanged after adjustment for covariates. The most effective combination of multiple prophylactic drugs in reducing DCI related to cerebral vasospasm was cilostazol, fasudil, and statin (0.38; 0.22–0.67; 0.005). Conclusions This study elucidated the trends in prophylactic drugs to prevent cerebral vasospasm and frequency of DCI after aneurysmal SAH in Japan. Coil embolization and cilostazol administration showed effectiveness in reducing DCI related to cerebral vasospasm in 2021.